The importance of interdisciplinary collaboration in advanced therapy of odontogenic cysts: A 31 Month follow-up case report - Kinga Bérczy; Csilla Erdei; Hajnalka Rajnai; Gergely Hriczó-Koperdák; Árpád Fancsaly-Joób; Noémi Kovács (Heliyon)
In this case report, we present the treatment of a 39-year-old male patient with a bilateral maxilla cyst diagnosed as an additional finding ont he X-ray. Both conservative dentistry treatments and oral surgical procedures were carried out using state-of-the-art materials and equipment, and in close collaboration with the other dental specialists. Endodontic treatment of the remaining teeth was performed before the oral surgery treatment. The root canal fillings were made using bioceramic-based root canal sealer. Cystectomy was then performed on both sides and the bone cavities were filled with platelet-rich fibrin (PRF). In the 4th month X-ray after the operation, radiological images showed bone regeneration. After 31 months, the periapical region is intact on the X-ray, the function of the root canal treated teeth has been preserved and the patient is free of complaints. With the chosen therapy we achieved a complication-free, long-term successful result in a time-efficient manner.